Alexander Pope and his eighteenth century women readers - Thomas, Claudia N. (Southern Illinois Univ. Press, 1994)
Throughout the 1980s, scholars debated Alexander Pope's attitude toward women by applying such critical methods as Marxist or deconstructionist theories to his texts. In this book, Claudia N. Thomas instead adopts reader-response theory in order to present what she regards as a more accurate analysis, mindful of the historical reception of Pope's various works. Thomas specifically responds to modern allegations that Pope was a misogynist and a literary victimizer of women. If Pope thought women inconsequential, she argues, why did he bother to cultivate a female audience? Furthermore, how did eighteenth-century women readers receive his writings? Thomas answers these questions by examining the literary responses to Pope of his eighteenth-century women readers: their prose responses to Pope, their poems addressed to him or replying to his poems, and their poems strongly influenced by him
Keywords: Pope, Alexander <1688-1744> -- Appreciation -- Great Britain; Pope, Alexander <1688-1744> -- Criticism and interpretation -- History -- 18th century; Pope, Alexander <1688-1744> -- Influence; Pope, Alexander -- 1688-1744; Geschichte 1700-1800; Geschichte 1709-1800; Frau; Geschichte; Authors and readers -- Great Britain -- History -- 18th century; English poetry -- Women authors -- History and criticism; English poetry -- 18th century -- History and criticism; Influence (Literary, artistic, etc.) -- History -- 18th century; Reader-response criticism; Verse satire, English -- History and criticism; Women and literature -- Great Britain -- History -- 18th century; Women -- Books and reading -- Great Britain -- History -- 18th century; Rezeption; Rezeptionsästhetik; Zeitgenossen; Leserin; Englisch; Schriftstellerin; Frauenliteratur; Großbritannien; England